Edukasi Kesehatan Reproduksi dan Pernikahan Dini pada Remaja di SMK MA'ARIF NU 2 Ajibarang - Maturan, Jessica Chressensia; Ningrum, Ema Wahyu; Haniyah, Siti (Universitas Harapan Bangsa, 2025)
Early marriage among adolescents remains a serious issue that affects social, psychological, physical, and reproductive health aspects. The low level of adolescent knowledge about reproductive health is one of the main factors contributing to the high incidence of early marriage. This community service activity aimed to improve the knowledge of female students at SMK Ma’arif NU 2 Ajibarang regarding reproductive health and the dangers of early marriage. The activity was conducted as part of a Community Service Program (PKM) consisting of three stages: preparation (material development and coordination with the school), implementation (education through interactive lectures and open discussions), and monitoring and evaluation (through pre-test and post-test) to assess the improvement in knowledge. A total of 44 students participated in the activity, which took place in August 2025 at SMK Ma’arif NU 2 Ajibarang. After the educational intervention, there was a significant increase in students’ knowledge. The average reproductive health knowledge score increased from 69.8 to 83.4, while knowledge about early marriage increased from 74.9 to 82.2. Reproductive health education through the PKM program proved effective in enhancing adolescents’ knowledge about reproductive health and the prevention of early marriage.